New trends in the recruitment of employeess in Czech ict organisations - Fajčíková, Adéla; Urbancová, Hana; Fejfarová, Martina (Univerzita Pardubice, 2018)
All organisations are facing the challenge of attracting and retaining employees whose skills and abilities are in line with the organisation’s needs. The plan of recruitment of human resources should be flexible, differentiate between individual categories of employees and should follow new trends in this area. The main objective of this paper is to identify the methods for the recruitment and selection of employees in Czech organisations and evaluate the differences in employee recruitment in large information and communication technology organisations (ICT) compared to other organisations active in the tertiary sector of the economy. The data was obtained through quantitative (n = 288) and qualitative (n = 34) research. Results of the survey show that organisations are starting to utilise a broader scale of methods to attract employees, in particular specialists, in ICT. Most of the organisations active in this area are struggling with the low number of job candidates on the labour market; to overcome this obstacle, they are developing and training their current staff (61.8%), changing their recruitment strategy and increasing initial salaries (50%). The research also identified 5 factors that define groups of organisations based on the methods they use to acquire new employees.
Keywords: Czech republic; differentiation of employees; human resource management; information and communication technology; recruitment and selection methods; M12; M15; O15